A biogas in-situ upgrading catalyst for producing biogas and its preparation method
By optimizing the catalyst components and preparation process, a catalyst with high reaction activity, high selectivity, hydrogen sulfide resistance, oxygen resistance and high stability was prepared, which solved the problem that the existing catalysts had low reaction activity, poor selectivity, easy poisoning and stable reactions. The problem of poor performance has achieved the improvement of biogas quality efficiency and cost.
Patent Information
- Application Number
- CN202410686981.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing biogas quality improvement catalysts have low reaction activity, poor selectivity, susceptible to hydrogen sulfide and oxygen, and poor stability in actual applications, which seriously restrict the efficiency and economics of the biogas quality improvement process.
By optimizing the catalyst components and preparation process, a high reactive, high selectivity, hydrogen sulfide resistance, oxygen resistance and high oxygen resistance are prepared by synergistic action of palladium, rhodium and nickel-based alloys, combined with the combination of cerium, boron and activated carbon. Stability catalyst.
It significantly improves the quality efficiency of biogas, reduces operating costs, extends the service life of the catalyst, and improves the yield and purity of biogas.
Smart Images

Figure CN118663272B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a biogas in-situ upgrading catalyst for preparing biogas and a preparation method thereof. Background Art
[0002] Biogas is an important renewable energy source, mainly composed of methane (CH4) and carbon dioxide (CO2), and usually contains small amounts of impurities such as hydrogen sulfide (H2S), nitrogen (N2), and water vapor. Biogas can be produced by anaerobic digestion of organic matter such as agricultural waste, animal manure, and sludge. However, untreated biogas has a low calorific value and a high impurity content. Direct use is not only inefficient, but also corrosive and polluting to equipment. Therefore, upgrading the quality of biogas (mainly decarbonization) to increase its calorific value and purity is the key to achieving its efficient utilization.
[0003] Traditional methods for improving the quality of biogas include physical adsorption, chemical absorption and membrane separation technologies. Although these methods can remove impurities and improve the quality of biogas to a certain extent, they usually require multiple steps, complex processes, and high costs. In addition, they are prone to equipment corrosion and catalyst poisoning when processing sulfur-containing biogas, affecting the quality improvement effect and equipment life.
[0004] Chemical catalysts are used to convert biogas CO2 into methane for biogas decarbonization and quality improvement, achieving the goals of carbon fixation, emission reduction and resource utilization simultaneously. The development of efficient and stable catalysts can not only improve the conversion efficiency of CO2 and increase the output of methane, but also effectively remove impurities such as hydrogen sulfide. However, existing catalysts generally have problems such as low reaction activity, poor selectivity, susceptibility to hydrogen sulfide and oxygen poisoning, and poor stability in practical applications, which seriously restrict the efficiency and economy of biogas quality improvement processes.
[0005] In order to overcome these deficiencies, the present invention provides a novel catalyst for in-situ upgrading of biogas to produce biogas and a preparation method thereof. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a biogas in-situ upgrading catalyst for producing biogas and a preparation method thereof. By optimizing the catalyst components and the preparation process, the catalyst has excellent performance in terms of high reactivity, high selectivity, resistance to hydrogen sulfide, resistance to oxygen and high stability, thereby effectively improving the biogas upgrading efficiency, reducing operating costs and extending the service life of the catalyst.
[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a biogas in-situ upgrading catalyst for producing biogas, the catalyst comprising the following components and their proportions:
[0008] Palladium (Pd): 2-5wt%;
[0009] Rhodium (Rh): 1-3wt%;
[0010] As precious metal components, palladium and rhodium show high catalytic activity under low temperature conditions, which can effectively promote the methanation reaction of CO2 in biogas to generate methane (CH4). In addition, palladium and rhodium have high selectivity for methanation reaction, which can minimize the generation of by-products and improve the purity of biogas.
[0011] The precious metals palladium and rhodium provide active sites on the catalyst surface, which promote the methanation reaction by adsorbing and activating the reactant molecules (CO2 and H2). The synergistic effect of palladium and rhodium can enhance the activity and selectivity of the catalyst.
[0012] Nickel-based alloy (Ni-Al): 15-25wt%; wherein, in the nickel-based alloy, aluminum accounts for 5-10% of nickel.
[0013] Nickel-based alloy is the main active metal. Compared with precious metals, nickel is a lower-cost catalyst material, but it also has high methanation activity. At the same time, the alloy formed by nickel and aluminum can improve the mechanical strength and thermal stability of the catalyst and extend the service life of the catalyst. The introduction of aluminum into the nickel-based alloy helps to improve the catalyst's anti-sulfurization performance.
[0014] Nickel-based alloys promote the adsorption and conversion of CO2 by providing a large number of active sites. The addition of aluminum not only improves the mechanical strength and stability of nickel-based alloys, but also reacts with hydrogen sulfide (H2S) to generate stable aluminum sulfide, protecting the active sites of nickel from being easily sulfided.
[0015] Cerium (Ce): 5-10wt%;
[0016] As a rare earth element additive, cerium has strong antioxidant properties and can maintain the stability of the catalyst in an oxygen-containing environment to prevent catalyst deactivation. At the same time, cerium can provide additional redox sites during the catalytic process, promote the reaction, and improve catalytic efficiency.
[0017] Cerium through its redox cycle It provides additional redox active sites (oxygen vacancies), enhancing the redox ability of the catalyst during the reaction. At the same time, the antioxidant properties of cerium can protect the active metal components of the catalyst under oxygen-containing conditions and prevent them from being oxidized and deactivated.
[0018] Boron (B): 0.5-2wt%;
[0019] Boron (B) acts as a promoter. Boron can react with hydrogen sulfide to generate stable boron sulfide, which protects the active sites on the catalyst surface from being sulfided. At the same time, the addition of boron can improve the surface properties of the catalyst and increase the activity and stability of the catalyst.
[0020] Boron forms a stable sulfide protective layer on the catalyst surface to prevent hydrogen sulfide from poisoning the catalyst. At the same time, the presence of boron can also adjust the electron density and physical and chemical properties of the catalyst surface and improve the overall performance of the catalyst.
[0021] Carrier material: activated carbon, accounting for 50-70wt% of the total weight of the catalyst;
[0022] As a carrier material, activated carbon has a highly developed pore structure and a large specific surface area, which can provide more active sites. At the same time, activated carbon has high thermal stability and can maintain its structure unchanged under high temperature conditions. And activated carbon has good mechanical strength and can withstand high pressure and mechanical shock in industrial reactors.
[0023] Activated carbon provides a large number of dispersion sites for active metal components through its high specific surface area and porous structure, effectively improving the activity and stability of the catalyst. At the same time, the good thermal stability and mechanical strength of activated carbon ensure the long-term stable operation of the catalyst in industrial applications.
[0024] Through the above technical solution, the synergistic effect of palladium, rhodium and nickel-based alloy significantly improves the methanogenic reaction activity and selectivity of the catalyst, which can effectively improve the yield and purity of biogas. At the same time, the addition of aluminum and boron in the nickel-based alloy significantly enhances the anti-sulfurization performance of the catalyst and extends the service life of the catalyst. And the introduction of cerium improves the antioxidant performance of the catalyst, ensuring the stability and activity of the catalyst in an oxygen-containing environment. In addition, activated carbon as a carrier material not only provides abundant active sites, but also has excellent thermal stability and mechanical strength, ensuring the long-term stable operation of the catalyst under high temperature and high pressure conditions.
[0025] Preferably, the ratio of Ni to Al in the nickel-based alloy is 90:10 to 95:5, and this ratio is intended to maximize the performance of the catalyst, including reaction activity, sulfur resistance and structural stability.
[0026] Nickel is a known effective catalytic active center, especially in methanation reactions. Increasing the proportion of nickel helps to provide more active sites, thereby enhancing the overall activity of the catalyst. At this preferred ratio, the nickel content is sufficient to ensure sufficient reaction activity, while the presence of aluminum prevents excessive aggregation of nickel, thereby maintaining high dispersion of the catalyst.
[0027] The addition of aluminum to nickel-based alloys is essential for improving the hydrogen sulfide tolerance of the catalyst. Aluminum can react with hydrogen sulfide to form a stable aluminum sulfide layer, protecting nickel from sulfidation, thereby maintaining the long-term activity and stability of the catalyst. The aluminum ratio is optimized to provide sufficient anti-sulfidation protection without excessively sacrificing the catalytic activity of nickel.
[0028] The introduction of aluminum also helps to enhance the structural stability of the catalyst. Under high temperature conditions, aluminum can help stabilize the crystal structure of nickel to prevent structural collapse or over-sintering during the reaction. Within this ratio range, the aluminum content is sufficient to ensure the structural stability of the catalyst without negatively affecting the catalytic activity.
[0029] Through the above technical solution, this ratio can not only give full play to the catalytic activity of nickel, but also enhance the anti-sulfurization performance and structural stability of the catalyst by adding an appropriate amount of aluminum. The design of this preferred ratio is based on comprehensive consideration of catalyst performance, including improving reaction activity, selectivity and stability in long-term operation, so that the catalyst can show better performance in the process of biogas upgrading.
[0030] Preferably, the activated carbon is acid washed and heat treated, the acid washing uses a 1-2M hydrochloric acid solution, the heat treatment temperature is 200-300°C, and the duration is 2-4 hours. The purpose of these steps is to remove impurities on the surface of the activated carbon, improve its physical stability and chemical activity, thereby improving the overall efficiency and durability of the catalyst.
[0031] High temperature treatment helps to remove residual volatile organic components in activated carbon, which may cause performance degradation during the catalytic process. The treated activated carbon shows better resistance in high temperature catalytic reactions, reducing physical wear and chemical corrosion.
[0032] Through the above technical solution, not only the surface properties of activated carbon are significantly improved, but also a solid foundation is provided for the performance optimization of the entire catalyst system, making it more suitable for biogas upgrading operations in industrial applications and improving the output and quality of biogas.
[0033] Preferably, the metal components in the catalyst are uniformly distributed on the surface of the support material by a co-precipitation method, which can effectively enhance the overall performance of the catalyst by providing uniform active sites, thereby enhancing its reaction activity and stability.
[0034] step:
[0035] Solution preparation: Firstly, metal precursors of palladium, rhodium, nickel-based alloy and cerium are dissolved in a suitable solvent according to a preferred ratio to form a solution.
[0036] Carrier preparation: After acid washing and heat treatment, the activated carbon carrier is placed in the precursor solution.
[0037] Adjust pH: Gradually adjust the pH value of the solution so that the metal ions are co-deposited on the surface of the activated carbon to form metal hydroxides.
[0038] Drying and calcination: The coprecipitated support is dried at room temperature and then calcined at a predetermined temperature to remove moisture and organic matter and form metal oxides.
[0039] Reduction treatment: Further treatment in a reducing atmosphere to convert metal oxides into metals.
[0040] Through the above technical scheme, the prepared catalyst not only has high reactivity and high selectivity, but also shows excellent stability and durability, which is very suitable for the application needs of in-situ upgrading of biogas to produce biogas. This method provides an efficient, economical and environmentally friendly catalyst preparation method suitable for large-scale industrial applications.
[0041] The present invention also provides a method for preparing a biogas catalyst by in-situ upgrading of biogas, comprising the following steps:
[0042] S1. Mix the precursor solutions of palladium, rhodium, nickel-based alloy and cerium, with a total solution concentration of 0.1-0.5M; this step is intended to ensure uniform dispersion of the metals for subsequent co-precipitation.
[0043] S2. Immerse the treated activated carbon carrier in the precursor solution for 6-12 hours; ensure that the precursor solution is evenly distributed on the surface of the activated carbon carrier.
[0044] S3. Dry the impregnated carrier at room temperature for 12 hours, and then dry it at 110° C. for 3-6 hours to remove moisture from the surface and pores of the carrier to prevent cracks or damage during subsequent high-temperature treatment.
[0045] S4, calcining in air at 350-450°C for 2-4 hours, and then reducing calcining at 400-500°C for 1-3 hours; the metal precursor is converted into metal oxides through the calcining step, and then converted into metal forms in a reducing environment, and these metal forms are active sites for catalytic reactions.
[0046] S5. Introduce boride, mix and heat in hydrogen atmosphere at 350-400℃ for 1-2 hours; the addition of boride is to improve the anti-sulfidation and stability of the catalyst. Boron can react with hydrogen sulfide to form stable sulfide to protect the active metal.
[0047] The above technical scheme ensures the high performance and long-term stability of the catalyst. The prepared catalyst has excellent catalytic activity and anti-sulfurization ability, and is very suitable for the conversion process of biogas upgrading to biogas. This method not only improves the service life of the catalyst, but also maintains high efficiency and environmental friendliness, and is an ideal choice for biogas upgrading in industrial applications.
[0048] Preferably, the precursor solution uses water or anhydrous ethanol as a solvent.
[0049] Water is one of the most commonly used solvents, with the advantages of low cost and easy availability. In addition, many metal salts have good solubility in water, which helps to prepare high-concentration uniform precursor solutions. At the same time, water is a non-toxic solvent, safe to use, and meets environmental protection requirements.
[0050] Anhydrous ethanol has a low boiling point (about 78°C), which facilitates rapid evaporation in the subsequent drying step, reducing energy consumption. At the same time, ethanol can effectively dissolve a variety of metal organic and inorganic salts, while helping metal ions to be more evenly distributed on the carrier surface. And compared with water, ethanol as an organic solvent, its compatibility provides a better environment for certain sensitive chemicals or metal precursors.
[0051] Through the above technical solution, the present invention not only improves the preparation efficiency of the precursor solution and the uniformity of the catalyst, but also takes into account environmental friendliness and economical operation. The selection of this solvent ensures the uniform distribution and high efficiency of the catalyst precursor, so that the final catalyst exhibits better activity and stability in the biogas upgrading process.
[0052] Preferably, the reduction roasting step is carried out in a hydrogen atmosphere with a hydrogen concentration of 5-10 vol%.
[0053] Excessive hydrogen concentration may cause the metal to be too active, which may lead to oxidation or rapid deactivation during the reaction. Controlling the hydrogen concentration helps to balance the activity and stability of the catalyst. Hydrogen is highly flammable, and controlling it within a lower concentration range (5-10 vol %) can reduce safety risks during the processing process.
[0054] The right amount of hydrogen can effectively reduce metal oxides to metals, which is the key to catalytic activity. Calcination in a hydrogen atmosphere reduces metal oxides to a purer metal form, improving the activity and reaction efficiency of the catalyst.
[0055] Reduction in a hydrogen environment can effectively remove oxygen from metal oxides while protecting support materials such as activated carbon from damage.
[0056] Through the above technical solution, the reduction calcination step of the catalyst not only enhances the activity and stability of the catalyst, but also improves the overall safety. This step is a key link to ensure that the catalyst can efficiently convert biogas into biogas, affecting the performance and service life of the final catalyst.
[0057] The present invention also provides a method for preparing biogas by in-situ upgrading of biogas, comprising the following steps:
[0058] S10, loading the catalyst into a fixed bed reactor; the catalyst is uniformly filled in the reactor in an appropriate form (such as granules or blocks) to ensure that the gas flow can be effectively distributed, maximize the contact area, and avoid flow resistance caused by excessive pressure. Its design can ensure that the gas passes through the catalyst bed evenly to achieve efficient contact and reaction.
[0059] S20, passing the gas containing biogas through the fixed bed reactor, the reaction temperature is 250-350°C, the pressure is 1-5atm, and the space velocity is 500-3000h -1 In a fixed bed reactor, the carbon dioxide in the biogas is converted into methane using a loaded catalyst, while impurities such as hydrogen sulfide are removed at the same time.
[0060] Through the above technical solution, this method can effectively convert carbon dioxide in biogas into methane, increase the calorific value of biogas, make it closer to the properties of natural gas, and thus improve its value and competitiveness in the energy market. At the same time, this method can also reduce CO2 emissions caused by biogas decarbonization and quality improvement, which has significant environmental benefits.
[0061] Preferably, the biogas contains 0.1-1% H2S.
[0062] Hydrogen sulfide concentrations of 0.1-1% cover most practical application scenarios, while this level is low enough to mitigate toxic effects on catalysts, yet high enough to require specific treatment strategies.
[0063] Through the above technical solution, the method not only improves the energy value of biogas, but also increases environmental benefits and equipment operation stability by removing hydrogen sulfide. Through this method, the economy and practicality of biogas as a renewable energy source can be greatly improved, especially in an environment with high sulfur content.
[0064] The present invention provides a biogas in-situ upgrading catalyst for producing biogas and a preparation method thereof. It has the following beneficial effects:
[0065] 1. The present invention can significantly improve the efficiency of the methanation reaction by optimizing the ratio of palladium, rhodium and nickel-based alloy, showing excellent CO2 conversion capacity and high methane yield. This high efficiency makes the biogas upgrading process more economical and efficient, reducing energy consumption.
[0066] 2. The catalyst of the present invention can highly selectively convert CO2 in biogas into methane, while effectively inhibiting the generation of by-products, thereby improving the purity of biogas. The excellent selectivity ensures the high quality of the product, making it more suitable for direct application in the energy market.
[0067] 3. The present invention enhances the tolerance of the catalyst to hydrogen sulfide by adding cerium and boron elements, prevents the catalyst from being poisoned in the presence of hydrogen sulfide, and prolongs the service life of the catalyst. This characteristic is particularly suitable for biogas sources with high sulfur content, reducing the dependence on desulfurization technology.
[0068] 4. The present invention provides high specific surface area and good thermal stability by using activated carbon that has been acid-washed and heat-treated as a carrier. The activated carbon is not only resistant to high temperatures, but also has excellent mechanical strength, ensuring the structural stability and compressive resistance of the catalyst during long-term operation.
[0069] The present invention adopts a coprecipitation method and a reasonable roasting and reduction step, and the preparation process is relatively simple and controllable, and is suitable for large-scale industrial production. This preparation method not only reduces production costs, but also ensures the quality and performance consistency of the catalyst, providing the possibility for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a 100 nm scale TEM image of the catalyst of Example 5 of the present invention;
[0071] Figure 2 This is a TEM image of the catalyst of Example 5 of the present invention at a scale of 20 nm;
[0072] Figure 3 This is a TEM image of the catalyst of Example 5 of the present invention at a 5 nm scale. DETAILED DESCRIPTION
[0073] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0074] Example 1: Basic biogas upgrading catalyst
[0075] Catalyst composition
[0076] Palladium: 2wt%
[0077] Rhodium: 1wt%
[0078] Nickel-based alloy: 15wt% (Ni:Al ratio is 90:10)
[0079] Cerium: 5wt%
[0080] Boron: 0.5wt%
[0081] Support material: activated carbon, accounting for 70wt% of the total weight of the catalyst
[0082] Preparation method
[0083] S1: palladium, rhodium, nickel-based alloy and cerium nitrate precursor solutions are mixed, the total concentration of the solution is 0.1 M, and anhydrous ethanol is used as the solvent.
[0084] S2: The activated carbon washed with acid and heat treated at 200 °C for 2 h was immersed in the precursor solution for 6 h.
[0085] S3: The impregnated support was dried at room temperature for 12 hours and then at 110°C for 3 hours.
[0086] S4: calcined in air at 350°C for 2 hours, and then reduction calcined in a 5 vol% hydrogen atmosphere at 400°C for 1 hour.
[0087] S5: Boric acid is introduced, and after mixing, heat treatment is performed in a hydrogen atmosphere at 350° C. for 1 hour.
[0088] Example 2: Enhanced biogas upgrading catalyst
[0089] Catalyst composition
[0090] Palladium: 5wt%
[0091] Rhodium: 3wt%
[0092] Nickel-based alloy: 25wt% (Ni:Al ratio is 95:5)
[0093] Cerium: 10wt%
[0094] Boron: 2wt%
[0095] Support material: activated carbon, accounting for 50wt% of the total weight of the catalyst
[0096] Preparation method
[0097] S1: The total concentration of the precursor solution is 0.5 M, and water is used as the solvent.
[0098] S2: After being pickled in 1 M hydrochloric acid solution and heat treated at 300 °C for 4 h, the activated carbon was immersed in the precursor solution for 12 h.
[0099] S3: Drying at room temperature for 12 hours, and then drying at 110°C for 6 hours.
[0100] S4: calcining in air at 450°C for 4 hours, followed by reduction calcining in a 10 vol% hydrogen atmosphere at 500°C for 3 hours.
[0101] S5: Using sodium borohydride, heat treatment is performed in a hydrogen atmosphere at 400° C. for 2 hours.
[0102] Example 3: Medium-strength biogas upgrading catalyst
[0103] Catalyst composition
[0104] Palladium: 3.5wt%
[0105] Rhodium: 2wt%
[0106] Nickel-based alloy: 20wt% (Ni:Al ratio is 92:8)
[0107] Cerium: 7.5wt%
[0108] Boron: 1.25wt%
[0109] Support material: activated carbon, accounting for 60wt% of the total weight of the catalyst
[0110] Preparation method
[0111] S1: The total concentration of the precursor solution is 0.3 M, and the solvent is water.
[0112] S2: The activated carbon was first pickled with 1.5M hydrochloric acid and then heat treated at 250°C for 3 hours. The immersion time was 9 hours.
[0113] S3: Dry at room temperature for 12 hours and at 110°C for 4.5 hours.
[0114] S4: calcining in air at 400°C for 3 hours, and then reduction calcining in a 7.5 vol% hydrogen atmosphere at 450°C for 2 hours.
[0115] S5: Boric acid is introduced and heat treatment is performed in a hydrogen atmosphere at 350°C for 1.5 hours.
[0116] Example 4: Low-cost biogas upgrading catalyst
[0117] Catalyst composition
[0118] Palladium: 2.5wt%
[0119] Rhodium: 1.5wt%
[0120] Nickel-based alloy: 18wt% (Ni:Al ratio is 90:10)
[0121] Cerium: 6wt%
[0122] Boron: 1wt%
[0123] Support material: activated carbon, accounting for 65wt% of the total weight of the catalyst
[0124] Preparation method
[0125] S1: Use 0.25 M water-soluble precursor solution.
[0126] S2: The activated carbon was acid-washed with 1M hydrochloric acid, heat-treated at 250°C for 3 hours, and then impregnated for 8 hours.
[0127] S3: Dry at room temperature for 12 hours and at 110°C for 4 hours.
[0128] S4: calcination in air at 375°C for 3 hours, and reduction calcination in 5 vol% hydrogen atmosphere at 450°C for 2 hours.
[0129] S5: Boric acid was used and heated in a hydrogen atmosphere at 375° C. for 1.5 hours.
[0130] Example 5: High-efficiency biogas upgrading catalyst
[0131] Catalyst composition
[0132] Palladium: 4.5wt%
[0133] Rhodium: 2.5wt%
[0134] Nickel-based alloy: 22wt% (Ni:Al ratio is 93:7)
[0135] Cerium: 8.5wt%
[0136] Boron: 1.75wt%
[0137] Support material: activated carbon, accounting for 55wt% of the total weight of the catalyst
[0138] Preparation method
[0139] S1: The total concentration of the precursor solution is 0.4 M, and anhydrous ethanol is used as the solvent.
[0140] S2: The activated carbon was pickled with 1.5M hydrochloric acid and heat treated at 275°C for 3.5 hours, and then impregnated for 10 hours.
[0141] S3: Dry at room temperature for 12 hours and at 110°C for 5 hours.
[0142] S4: calcining in air at 425°C for 3.5 hours, followed by reduction calcination in 8 vol% hydrogen atmosphere at 475°C for 2.5 hours.
[0143] S5: Sodium borohydride was introduced and heated in a hydrogen atmosphere at 375°C for 1.75 hours.
[0144] TEM electron microscope analysis of the catalyst prepared in Example 5:
[0145] like Figure 1-Figure 3 As shown, TEM images at scales of 100 nm, 20 nm and 5 nm are shown respectively.
[0146] Among them, Figure 1 shows that the nanoparticles in the catalyst of Example 5 are aggregated in the form of larger clusters. This structure shows that although there is a certain sintering or fusion phenomenon between the particles, the overall cluster distribution is well maintained, and the particle size distribution range is 10-20nm, which provides a diverse reaction environment for the functional area of the catalyst.
[0147] This larger cluster morphology helps to increase the high temperature resistance of the catalyst and also indicates the result of the interaction between particles during the preparation process, which is of great significance for the quality improvement of biogas under high temperature reaction conditions.
[0148] in, Figure 2 The uniform distribution of the metal particles in the catalyst of Example 5 on the support is shown. The particle size is small (less than 5 nm on average) and the distribution is relatively uniform. This uniform nanoscale distribution helps to provide more active sites, thereby enhancing the reactivity and selectivity of the catalyst.
[0149] The uniform distribution and appropriate nano-size of the metal particles are key factors in achieving high CO2 conversion and excellent methane yield. This shows that the catalyst of the present invention optimizes the dispersion of the active components in design and preparation, which helps it to perform well in the biogas upgrading process.
[0150] in, Figure 3 High-resolution details of the metal particles of the catalyst of Example 5 are provided, clearly showing the lattice structure of individual nanoparticles. This high-resolution image reveals the crystal structure of the particles, which is crucial for understanding the electronic properties of the catalyst and the catalytic mechanism.
[0151] The well-defined lattice structure confirms the high crystallinity of the active metal components in the catalyst, which is generally associated with higher catalytic activity and more stable catalytic performance. Therefore, the catalyst of Example 5 shows excellent catalytic efficiency and stability in biogas upgrading.
[0152] Through TEM analysis of the catalyst in Example 5 at different scales, it can be seen that the catalyst has excellent microstructural characteristics and a large specific surface area (BET test shows that it is greater than 100 m 2 / g), from large-scale cluster structures to the lattice structure of individual particles, these features work together to improve the comprehensive performance of the catalyst. The optimized design of these microstructures is the key to the efficient conversion of CO2 and removal of H2S by the catalyst in Example 5, giving it obvious application advantages in the field of biogas quality improvement.
[0153] Experiment 1: Comparison of catalytic activity and methane yield
[0154] Purpose: To compare the methane yields of different example catalysts under the same operating conditions to demonstrate the efficiency of each catalyst formulation.
[0155] Experimental steps:
[0156] Preparation: Prepare a fixed bed reactor; prepare a standard biogas mixture, the main components of which are CH4, CO2, and 0.5% H2S. Electrolyze water to produce high-purity hydrogen for hydrogen source, with a concentration greater than 99.9%.
[0157] Catalyst loading: The catalysts of five different embodiments (embodiments 1-5) were loaded into a fixed bed reactor respectively, and the loading amount of each catalyst was kept consistent.
[0158] Set the reaction conditions: reaction temperature: 300℃; pressure: 3atm; space velocity: 1500h -1 .
[0159] Experimental operation: Start the reactor and ensure that the gas flows through the catalyst bed. Record the start time and collect gas samples at each time point (0.5 hours, 1 hour, 1.5 hours, 2 hours).
[0160] Sample analysis: The gas samples collected at each time point were analyzed using a gas chromatograph (GC) to measure the concentration of methane (CH4).
[0161] The experimental results are shown in Table 1:
[0162] Table 1 Comparative data of CO2 methanation single-pass conversion rate of catalysts in Examples 1-5
[0163]
[0164] It can be observed from the experimental data that under the same operating conditions, the conversion rates of methane in the CO2 methanation single-pass conversion process are significantly different for catalysts of different embodiments. The specific analysis is as follows:
[0165] Example 5: shows the highest methane yield, especially reaching a peak of 87% at 2.0 hours. This high conversion rate is due to the use of a specific catalyst formulation and an optimized metal component ratio in Example 5, which effectively increases the high conversion rate of CH4.
[0166] Example 2 also showed a relatively high conversion rate, especially reaching 85% at 2.0 hours, which indicated that the catalyst formulation was very effective in promoting the methanation reaction.
[0167] Example 3: The performance was stable throughout the experiment, and the methane yield remained between 76-80%, showing consistent catalytic activity.
[0168] Example 1 and Example 4: Although the conversion rate is low, they still show effective catalytic activity, especially Example 1 achieves a methane yield of 76% in 2.0 hours, while Example 4 is slightly lower than this.
[0169] Overall, the excellent performance of Example 5 and Example 2 highlights the success of their catalytic formulations and process optimization in improving the efficiency of the methanation reaction. Example 3 provides a stable solution, and although Example 1 and Example 4 are less efficient, they may still be applicable under cost control or specific application requirements. These data emphasize the importance of optimizing catalyst composition and preparation conditions in improving the decarbonization and quality improvement of biogas.
[0170] Experiment 2: CO2 conversion rate test
[0171] Purpose: To compare the CO2 conversion efficiency of catalysts in different examples to evaluate their quality improvement capabilities.
[0172] The experimental steps are basically the same as those of Experiment 1, except that a gas chromatograph is used to analyze the gas samples collected at each time point during sample analysis to measure the concentration of CO2.
[0173] The experimental results are shown in Table 2:
[0174] Table 2 Comparative data of CO2 conversion rate of catalysts in Examples 1-5
[0175]
[0176] This set of data shows the performance differences of catalysts in different embodiments in terms of CO2 conversion rate. The specific analysis is as follows:
[0177] Example 5: shows the highest CO2 conversion rate, reaching 80% and 82% at 1.0 hour and 2.0 hour time points, which is significantly higher than other examples. This shows that the catalyst formulation and preparation method of Example 5 are very effective in improving CO2 conversion efficiency.
[0178] Example 2 also exhibits a relatively high conversion rate, especially reaching 81% at 2.0 hours, which reflects its high catalytic activity, which may be due to the use of a relatively high proportion of active metal components.
[0179] Example 3: Stable performance was maintained throughout the experiment, and the CO2 conversion rate was maintained between 70-75%, showing good catalytic performance and consistency.
[0180] Example 1 and Example 4: Although the conversion rate is lower, they still show effective CO2 treatment capabilities, with the conversion rate fluctuating between 67-72%. This may be related to their lower precious metal content or different preparation processes, resulting in lower catalytic efficiency.
[0181] Overall, the excellent performance of Example 5 shows the potential of high-efficiency catalysts, especially suitable for applications with high CO2 conversion rates. Examples 2 and 3 provide higher performance options, suitable for industrial applications requiring higher stability and efficiency. Examples 1 and 4 may be suitable for cost-sensitive applications, although their conversion rates are lower, they may have advantages in cost control.
[0182] Experiment 3: Hydrogen sulfide treatment capacity
[0183] Purpose: To test the performance of catalysts of different embodiments in treating sulfur-containing biogas (H2S content of 0.1-1%).
[0184] The experimental steps are basically the same as those of Experiment 1, except that a gas chromatograph is used to analyze the gas samples collected at each time point during sample analysis to measure the concentration of H2S.
[0185] The experimental results are shown in Table 3:
[0186] Table 3 Comparative data of hydrogen sulfide removal rate of catalysts in Examples 1-5
[0187]
[0188]
[0189] This set of data shows the removal effect and efficiency of catalysts in different embodiments in treating biogas containing hydrogen sulfide. From the data, we can see that:
[0190] Example 2 is significantly better than the other examples, showing an extremely high hydrogen sulfide removal rate, which continues to increase throughout the experiment and reaches 87% removal rate at 2.0 hours. This is because its catalyst components and preparation process are specially optimized to enhance the reaction to hydrogen sulfide.
[0191] Example 5 also exhibited a very high removal efficiency, closely following Example 2, achieving 86% removal at 2.0 hours. This indicates that the catalyst formulation of Example 5 is very effective in treating hydrogen sulfide.
[0192] The removal rates of Examples 3 and 4 were relatively high and continued to increase, eventually reaching 77% and 75% at 2.0 hours. These data indicate that although these Examples are less efficient than the first two, they still have considerable hydrogen sulfide treatment capabilities.
[0193] Example 1 has the lowest hydrogen sulfide removal rate at each time point, but increases from 62% at 0.5 hour to 65% at 2.0 hour, showing a certain treatment potential, although relatively low.
[0194] In general, the high performance of Examples 2 and 5 highlights the special advantages of their catalysts in improving the efficiency of hydrogen sulfide removal, and is suitable for biogas upgrading applications with high sulfur content. Examples 3 and 4 provide a more balanced treatment effect, while Example 1 may be suitable for applications with low sulfur content or require further optimization to improve its hydrogen sulfide treatment capacity.
[0195] Experiment 4: Thermal stability and durability test
[0196] Purpose: To evaluate the stability and activity retention of catalysts from different examples during long-term operation.
[0197] The experimental procedure was basically the same as that of Experiment 1, except that the reactor was operated continuously for 100 hours without interrupting the gas flow, and gas samples were collected every 10 hours and the concentrations of methane and carbon dioxide were measured using a gas chromatograph (GC) to evaluate the catalytic activity.
[0198] The experimental data are shown in Table 4:
[0199] Table 4 Comparative data of activity decay rate of catalysts in Examples 1-5
[0200]
[0201] The activity decay percentage was calculated using the following formula:
[0202]
[0203] From the experimental data, it can be observed that all catalysts show activity decay under long-term operating conditions, but there are significant differences in durability between different examples:
[0204] Example 2 and Example 5: showed the lowest activity decay rate, with the activity decay of only 10% and 7% after 100 hours, which shows that the formulation and preparation process of these two catalysts are the best in maintaining long-term stability and high efficiency.
[0205] Example 3: The activity decay rate is moderate, and the activity decay is 15% after 100 hours, showing good stability and moderate durability.
[0206] Examples 1 and 4: Relatively high activity decay rates, reaching 20% and 21% respectively after 100 hours.
[0207] These results indicate that the catalysts of Examples 2 and 5 are very suitable for applications requiring long-term stable operation, such as industrial-scale biogas treatment facilities, while Examples 1 and 4 may require further optimization to improve their thermal stability and durability.
[0208] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A biogas in-situ upgrading catalyst for producing biogas, characterized in that: The catalyst comprises the following components and their proportions: Palladium: 2-5wt% Rhodium: 1-3wt% Nickel-based alloy: 15-25wt% Cerium: 5-10wt% Boron: 0.5-2wt% Carrier material: activated carbon, accounting for 50-70wt% of the total weight of the catalyst; The ratio of Ni to Al in the nickel-based alloy is 90:10 to 95:5; The activated carbon is acid washed and heat treated, wherein the acid wash uses a 1-2M hydrochloric acid solution, the heat treatment temperature is 200-300°C, and the duration is 2-4 hours.
2. A method for preparing a biogas in-situ upgrading catalyst for producing biogas, which is used to prepare the biogas in-situ upgrading catalyst for producing biogas as claimed in claim 1, characterized in that: The following steps are involved: S1, mixing the precursor solutions of palladium, rhodium, nickel-based alloy and cerium, with the total concentration of the solution being 0.1-0.5M; S2, immersing the treated activated carbon support in the precursor solution for 6-12 hours; S3, drying the impregnated support at room temperature for 12 hours, and then drying at 110° C. for 3-6 hours; S4, calcining in air at 350-450°C for 2-4 hours, and then reduction calcining at 400-500°C for 1-3 hours; S5. Introduce boride, mix and heat in a hydrogen atmosphere at 350-400°C for 1-2 hours.
3. The preparation method according to claim 2, characterized in that: The precursor solution uses water or anhydrous ethanol as a solvent.
4. The preparation method according to claim 2, characterized in that: The reduction roasting step is carried out in a hydrogen atmosphere with a hydrogen concentration of 5-10 vol%.
5. The preparation method according to claim 2, characterized in that: The boride is boric acid or sodium borohydride.
6. A method for producing biogas by in-situ upgrading of biogas, using the catalyst as claimed in claim 1, characterized in that: The following steps are involved: S10, loading the catalyst into a fixed bed reactor; S20, passing the gas containing biogas through the fixed bed reactor, the reaction temperature is 250-350°C, the pressure is 1-5atm, and the space velocity is 500-3000h -1 .
7. The method according to claim 6, characterized in that The biogas contains 0.1-1% H2S.
Citation Information
Patent Citations
Method for producing natural gas through methanation of synthesis gas by virtue of Raney alloy catalyst
CN106497619A
Methanation catalyst with sulfur tolerance and preparation method thereof
CN106622280A